Letter : Constantino Perez Bratos - Dukes, Charles
012a-0102-001 General Secretary: CHAS. DUKES (to whom all communications must be addressed) National Union of General and Municipal Workers 5 Ensleigh Gardens, London, W.C.1. National Industrial Officers H. Bullock H.N. Harrison Mark Hewitson T. Williamson, J.P. National Woman Officer Dorothy Elliott. J.P. April 8th 1938 Dear Sir Walter, Constantino Perez Bratos Thanks for yours of the 7th inst. and I will now await any further news which you may have to pass on in the near future. Yours sincerely, Chas Dukes General Secretary Sir Walter Citrine, K.B.E. General Secretary T.U.C. Transport House, Smith Square, S.W.1. 292/946/12a/102